Moral Values in Short Story “Ad-Dunya Riwayah” by Taufiq Al-Hakim - Zacky Aqsha Noriska; Al Farahil A’la; Nur Chalis; Ivan Aulia Trisnady; Suraiya Suraiya (Universitas Khairun, 2025)
The short story Ad-Dunya Riwayah by Taufiq al-Hakim depicts the transient nature of worldly life. The characters in this story are portrayed through the dynamics of life filled with inner conflicts, social interactions, and values that serve as life’s guiding principles. Through this narrative, Taufiq al-Hakim embeds moral messages related to human relationships with oneself and with others. Therefore, this study aims to describe the moral values contained in the short story Ad-Dunya Riwayah by Taufiq al-Hakim. These moral values are analyzed using Ferdinand de Saussure’s semiotic theory, which views a text as a system of signs consisting of the relationship between the signifier and the signified. The research employs a descriptive qualitative method through several stages: reading the text, identifying data in the form of words, phrases, clauses, and sentences that contain moral values, and then classifying them according to semiotic theory. The findings show that the short story Ad-Dunya Riwayah contains five positive moral values self-confidence, responsibility, keeping promises, affection, and politeness and two negative moral values despair and bullying. Thus, the short story Ad-Dunya Riwayah by Taufiq al-Hakim conveys numerous moral lessons that serve as valuable guidance for everyday life.